Negative-strand RNA viruses: The plant-infecting counterparts - Kormelink, Richard; Garcia, Maria Laura; Goodin, Michael; Sasaya, Takahide; Haenni, Anne-Lise (Virus research, 2011)
While a large number of negative-strand (−)RNA viruses infect animals and humans, a relative small number have plants as their primary host. Some of these have been classified within families together with animal/human infecting viruses due to similarities in particle morphology and genome organization, while others have just recently been/or are still classified in floating genera. In most cases, at least two striking differences can still be discerned between the animal/human-infecting viruses and their plant-infecting counterparts which for the latter relate to their adaptation to plants as hosts. The first one is the capacity to modify plasmodesmata to facilitate systemic spread of infectious viral entities throughout the plant host. The second one is the capacity to counteract RNA interference (RNAi, also referred to as RNA silencing), the innate antiviral defence system of plants and insects. In this review an overview will be presented on the negative-strand RNA plant viruses classified within the families Bunyaviridae, Rhabdoviridae, Ophioviridae and floating genera Tenuivirus and Varicosavirus. Genetic differences with the animal-infecting counterparts and their evolutionary descendants will be described in light of the above processes.